Main Components Of School Management Model Using Information And Communications Technologies - Antonyan, Lilit; Arakelyan, Narek (Զանգակ հրատ.)
This article is an attempt to cover the main components of ICTs’-based school management model, with special reference to the respective principles, styles, strategies, competencies, as well as their implementation and application mechanisms. An attempt is made to show how the content and functional characteristics of the mentioned components change during and as a result of the use of ICTs. The use of ICT in schools has become increasingly prevalent, and effective school management requires a comprehensive approach that integrates these tools into all aspects of operations. The article identifies the key components of this model, including communication systems, information management systems, learning management systems, and administrative management systems. The authors explore the benefits and challenges of implementing such a model and provide examples of successful applications. The efficiency of the proposed model is substantiated from the point of view of ensuring the organic connections of its components.
Keywords: Pedagogy